(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is concluded that Low sugar wheat bread can be prepared with different ratio of Refined Wheat Flour, Wheat Flour, Sago Flour and Stevia at different levels of concentration (T0, T1, T2, and T3). The concentration of T0 were 100:0:0; T1 were 75:22.5:2.5:1; T2 were 70:25:05:1 and T3 were 65:27.5:7.5:1. The data collected on different aspects were tabulated & analyzed statistically using the methods of variance & critical difference. Physicochemical analysis (Total solids, Ash, Carbohydrate, Protein, Fat, Fiber and Moisture) was done for estimating its nutritional content and for organoleptic characteristics (Color and Appearance, Body and Texture, flavor and Taste & Overall Acceptability) were judged by 9-point hedonic scale. The Cost Analysis of final product for treatments T0, T1, T2, and T3 were 17.00/-, 18.00/-, 18.50/- and 19.00/- Rs/200g respectively. According to Physicochemical analysis treatment T3 with ratio 65:27.5:2.5 was found to be the best among all with highest fiber content and T2 with 70:25:05:1 was best among all the treatment according to Organoleptic score.